99mTc-Pyrophosphate Scintigraphy Can Image Tracer Uptake in Skeletal Trunk Muscles of Transthyretin Cardiac Amyloidosis. (28th January 2023) - Takahashi, Koji; Hiratsuka, Yoshiyasu; Sasaki, Daisuke; Sakaue, Tomoki; Enomoto, Daijiro; Morioka, Hiroe; Uemura, Shigeki; Okura, Takafumi; Ikeda, Shuntaro; Kono, Taizo; Iwamura, Takaaki; Yamamura, Nobuhisa; et al.
Abstract : Purpose: 99m Tc-pyrophosphate ( 99m Tc-PYP) uptake in the skeletal muscles is minimal in patients with transthyretin cardiac amyloidosis (ATTR-CA) when assessed qualitatively and quantitatively. We previously demonstrated moderate- to high-grade 99m Tc-PYP uptake in the subcutaneous abdominal fat of some patients with ATTR-CA and showed that this abnormal finding could reflect the regional amyloid burden of this tissue. We aimed to investigate the frequency of 99m Tc-PYP uptake in skeletal trunk muscles of patients with ATTR-CA. Methods: Chest- and abdomen-centered 99m Tc-PYP scintigraphy images were obtained 2 hours after IV injections of the tracer (20 mCi) in 36 patients with ATTR-CA. The frequency of 99m Tc-PYP uptake in the following 11 skeletal trunk muscles was investigated: pectoralis major, deltoid, subscapularis, infraspinatus, trapezius, latissimus dorsi, erector spinae, psoas major, abdominal oblique, rectus abdominis, and the gluteus muscles. Results: Ten of the 11 muscles were involved in patients with the highest number of 99m Tc-PYP uptake in the skeletal trunk muscles examined, whereas no muscle was involved in a patient with the least uptake. The muscle with the highest rate of 99m Tc-PYP uptake, observed in 34 of 36 patients (94.4%), was the abdominal oblique. No tracer uptake was observed in the psoas major. The frequency of radiotracer uptake in the remaining examined muscles was between those of abdominal oblique and psoas major muscles. Conclusions: Radiotracer uptake was often detectable in some skeletal trunk muscles of ATTR-CA, although the muscles of patients examined and the skeletal trunk muscles of 1 patient showed heterogeneity in the uptake of 99m Tc-PYP.